2020
DOI: 10.1093/petrology/egaa028
|View full text |Cite
|
Sign up to set email alerts
|

Metasomatism and Hydration of the Oceanic Lithosphere: a Case Study of Peridotite Xenoliths from Samoa

Abstract: Water influences geodynamic processes such as melting, deformation and rheology. Yet its distribution in the oceanic upper mantle is primarily known indirectly from melt inclusions and glasses of erupted mantle melts (i.e. mid-ocean ridge and ocean island basalts). To better constrain the mechanisms influencing the distribution of H2O in the mantle, particularly regarding the role of metasomatism, we analyzed 15 peridotite xenoliths from Savaiʻi and 2 dunite xenoliths from Taʻū (Samoa) for structural H2O (by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 157 publications
3
25
1
Order By: Relevance
“…S1). This behavior is opposite to experimental predictions after partial melting ( 11 ) and to elemental trends observed in some xenoliths ( 28 ). Further, H 2 O negatively correlates with Ti and Na in both pyroxenes ( Fig.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…S1). This behavior is opposite to experimental predictions after partial melting ( 11 ) and to elemental trends observed in some xenoliths ( 28 ). Further, H 2 O negatively correlates with Ti and Na in both pyroxenes ( Fig.…”
Section: Resultscontrasting
confidence: 98%
“…Depending on the mechanism of hydrogen incorporation, xenoliths can show positive ( 56 ) or negative ( 54 ) correlations between H 2 O and ƒ o 2 so that oxidizing conditions under which xenoliths evolve are not a prediction for their water contents. Although mantle xenoliths are prone to melt-rock reactions ( 5 ), some retain broad positive correlations between H 2 O and other incompatible elements ( 28 , 61 ), opposite to the VLS time series. It is possible that, in xenoliths, a loss of Na + during melting would not necessarily be followed by H + addition from a percolating melt, as samples may re-equilibrate in the lithospheric mantle for millions of years before metasomatism and/or eruption occurs.…”
Section: Discussionmentioning
confidence: 99%
“…These models also show that decoupling of NAM water contents from their REE abundances (e.g., Warren and Hauri 2014;Peslier et al 2017;Ashley et al 2020 Unraveling the origin of the water contents measured in peridotite NAMs requires additional constraints on the history of the sample, including petrographic analysis and measurement of other trace elements.…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, there is evidence that the EM2 source has been enriched not only by addition of sediments, but also carbonatitic material. Carbonatitic metasomatism beneath Samoa has been proposed by many authors (Ashley, 2019; Ashley et al., 2020; Hauri et al., 1993; Hauri & Hart, 1994). Evidence for carbonatite metasomatism is clearest in Samoan mantle peridotite xenoliths that show evidence of interaction with carbonatitic liquids based on their LREE enrichment and Zr and Ti depletions in clinopyroxene (Hauri & Hart, 1994; Hauri et al., 1993).…”
Section: Discussionmentioning
confidence: 95%
“…Evidence for carbonatite metasomatism is clearest in Samoan mantle peridotite xenoliths that show evidence of interaction with carbonatitic liquids based on their LREE enrichment and Zr and Ti depletions in clinopyroxene (Hauri & Hart, 1994;Hauri et al, 1993). More recently, Ashley et al (2020) performed an analysis of water systematics and major and trace element characteristics in Samoa peridotite xenoliths (focusing on orthopyroxenes) revealing variable depletions in water contents of nominally anhydrous minerals, and in addition to their trace element characteristics, indicate metasomatism of carbonatitic and silicate liquids. Further, previous studies have suggested that partial melting of mantle enriched with carbonatitic liquids can result in phonolitic to trachytic liquids (Ashwal et al, 2016;Hauri et al, 1993;Loges et al, 2019;Tsuno and Dasgupta, 2011).…”
Section: 1029/2020gc009212mentioning
confidence: 99%